Action of Water-Insoluble Trypsin Derivatives on Fibrinogen Clottability - Alexander, B; Rimon, A; Katchalski, E (Thrombosis and Haemostasis, 1966)
Two water-insoluble derivatives of trypsin, one prepared by coupling polytyrosyl trypsin to diazotized p-amino-phenylalanine-leucine copolymer (IPTT), the other by coupling trypsin to ethylene maleic anhydride copolymer (IMET), quickly compromise the clotting of fibrinogen by thrombin, as does native trypsin. When used in equivalent caseinolytic or esterolytic activity IMET is much more potent than IPTT. The effects, temperature and concentration dependent, are blocked by trypsin inhibitors. Clotting kinetics are far more affected than the ultimate fibrin yield obtained by thrombin. Marked impairment of clottability is associated with cleavage of 1-2 peptide bonds of the fibrinogen molecule. The early changes are paralleled by release of very small amounts of TCA-soluble tyrosine-containing fragments, and associated with the appearance in the ultracentrifuge of a small amount of a fast sedimenting material. The electrophoretic mobility of the altered fibrinogen remains uniform, but it is significantly slower than the original intact fibrinogen. Fibrinogen that is exposed to the water-insoluble trypsin derivatives for relatively short time intervals will under certain conditions clot spontaneously, indicating that the trypsin splits inter alia the same bonds cleaved by thrombin. The differences between IPTT and IMET in their actions on fibrinogen are attributed to the different nature of the carrier to which trypsin is attached in these water-insoluble derivatives.